2017
DOI: 10.11604/pamj.2017.27.67.12427
|View full text |Cite
|
Sign up to set email alerts
|

Abcès du coude révélant la maladie des griffes du chat: à propos d’un cas

Abstract: La maladie des griffes du chat (MGC) apparaît comme une cause fréquente de lymphadénopathie chronique bénigne chez l'enfant et l'adulte jeune. L'agent responsable de la maladie est Bartonella henselae. Les symptômes habituels sont une lymphadénopathie régionale associée à une fièvre. Nous rapportons une observation cliniquement atypique et potentiellement trompeuse de MGC, révélée par un abcès du coude chez une fille de 18 ans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A French study conducted from 2009 to 2013 reported that the Comoros were the main focus of Mycobacterium leprae infections diagnosed in France [24], while in a study conducted in Madrid, from 1989 to 2015, most cases were migrants from South America [25] and in a Danish study conducted from 1980 to 2010, most cases were migrants from South-East Asia [26]. In our study, one Bartonella henselae case was diagnosed in a patient returning from Morocco, a disease rarely described in Morocco [27][28][29][30], while fleas have been shown to be positive for Bartonella henselae in this country [31].…”
Section: Discussionmentioning
confidence: 38%
“…A French study conducted from 2009 to 2013 reported that the Comoros were the main focus of Mycobacterium leprae infections diagnosed in France [24], while in a study conducted in Madrid, from 1989 to 2015, most cases were migrants from South America [25] and in a Danish study conducted from 1980 to 2010, most cases were migrants from South-East Asia [26]. In our study, one Bartonella henselae case was diagnosed in a patient returning from Morocco, a disease rarely described in Morocco [27][28][29][30], while fleas have been shown to be positive for Bartonella henselae in this country [31].…”
Section: Discussionmentioning
confidence: 38%